FORMULASI TERBAIK BROWNIES UBI UNGU SEBAGAI MAKANAN SELINGAN - Yahmi Ira Setyaningrum (ITKM WIDYA CIPTA HUSADA, 2024)
Purple sweet potato is one of the local potentials of Malang Raya, but its utilization is still relatively low. Snack foods made from local raw materials are still minimal, so innovation is needed to develop snacks made from purple sweet potatoes. This research aims to determine the best formulation of purple sweet potato brownies which will be developed as a snack for hospital patients. This experimental research method used a randomized block design (RAK) with one factor, namely the weight ratio of purple sweet potato and wheat flour, with four treatments including F0 (0: 200 gr), F1 (75 gr: 125 gr), F2 (100 gr: 100 gr). gr), F3 (150 gr: 50 gr). Data analysis used the Kruskal Wallis test with a level of 5%, followed by the Mann Whitney test. The research results showed that the best formulation was F3 based on the results of organolytic tests for color, taste, aroma and texture. F3 has met the snack food standards, with an energy value according to the nutritional adequacy figure for snacks of 10% of total energy or an average of 265 kcal. The greater the number of purple sweet potato substitutes used, the brighter the color acceptability, the sweeter the taste, the more characteristic aroma of sweet potatoes and the denser the texture. It is recommended to conduct research regarding the acceptability of the best formulation in this study with standard hospital snacks.